Digital Detox Tourism in the Lecturer Profession - pramadika ramanda; Syahrul Helmi Revaldo; Didik Usman Wibowo (PROGRAM STUDI PARIWISATA SYARAH, FAKULTAS EKONOMI DAN BISNIS ISLAM, UNIVERSITAS ISLAM NEGERI MATARAM, 2026)
Purpose: This study aims to analyze the level of interest, needs, and urgency of lecturers towards digital-free tourism and to map the potential for developing tourist areas in line with the concept of digital detox tourism. Method: This study employed a qualitative descriptive approach to explore lecturers’ experiences of digital fatigue and their perceptions of digital detox tourism as a recovery strategy. Primary data were collected through semi-structured interviews with lecturers selected using purposive sampling, while observations and documentation were used to support data triangulation. Secondary data from relevant literature were also reviewed to strengthen the analysis and provide a broader understanding of digital detox tourism within the context of academic work environments. Result: The findings reveal that lecturers generally perceive digital-free tourism as an important means of achieving psychological recovery. Informants highlighted the need for digital detox tourism activities, particularly those involving nature-based tourism and retreat programs. Family vacations and flexible leisure activities were also considered potential alternatives for reducing digital fatigue. These findings suggest that academic environments require more structured spaces and opportunities that support psychological recovery and well-being. Contribution: Conceptually, digital detox tourism not only serves as a means of recreation but also as an institutional strategy to support the well-being and productivity of academic staff. Universities are expected to integrate digital detox programs through academic retreats, mindfulness training, and clear digital working hours. Local governments can also develop digital-free tourism zones as part of sustainable tourism policies, while lecturers are expected to adopt a digital balance lifestyle independently. This study confirms that digital detox tourism has the potential to become a strategic instrument in building a healthy, adaptive, and resilient academic work ecosystem against digital pressures in the post-pandemic era.